Analysis of Simple Additive Weighting (SAW) Method for The Selection of The Best Teachers in SMK Siti Banun - Garit Mahardika; Marnis Nasution; Haris Munandar (Jurnal Mantik, 2021)
Solution and problem-solving processes may have decisions. Decision management services are designed to assist and support the decision-makers decision-making. They can be used in the decision-making process and assess the processes used in digital elections. Another method is the Simple Additive Weighting (SAW) method, often used in decision support systems. This SAW strategy was selected because it determines each attribute's weight before moving on to the ranking process and then selects the alternative with the highest weight from the alternatives list. This instance, instead, is to use the PEW (proportional weighted) method to determine the best teacher at SMK Siti Banun. using this scheme, you can assume that the rankings would be more reliable since it is based on pre-defined criteria and weights to provide the best results.